Gender and Adaptation Practices against Climate Change Impact on Agricultural Activities in Western Nepal - Dhungana, Ananta Raj; KC, Vikash Kumar; Khand, Purna Bahadur; Dhungana, Surya Mani (Journal of Development and Social Engineering, 2023)
There is a close association between gender and climate change adaptation practices. Climate change affects everyone but man and woman have different vulnerabilities and unequal capacity to deal with the adverse impact of climate change. The main objective of this paper is to assess the association between gender and adaptation practices against climate change impact on agriculture activities in western Nepal. A survey of 1046 households using semi-structured questionnaire using multistage sampling was used to collect quantitative data from five districts of western Nepal. Focus group discussion (FGDs) was also conducted to collect the qualitative data. Chi-squared test was used to find the association between gender and adaptation practices against climate change impact on agriculture activities in western Nepal. The analyses reveal that more men involve in agricultural activities. Among the several adaptation activities, gender matters for the use of improved irrigation facility, use of chemical fertilizer and use of cropping season.